The children, climate changes and the fairytale... without the fairies: children’s perception - Balcão, Liliane Mara Navarro; Balcão, Victor Manuel Cardoso Figueiredo; Duarte Carvalho Vila, Marta Maria (Ambiente & Educação: Revista de Educação Ambiental, 2026)
As crianças, as mudanças climáticas e o conto de fadas... sem as fadas: a percepção das crianças Climate change caused by anthropogenic actions plays a significant role in escalating the frequency and intensity of extreme environmental. Climate change threatens ecosystems, biodiversity, livelihoods, health, and well-being of future generations. The perception of young people and children about the climate crisis and its effects on the planet must be known to develop attractive educational practices and materials. For this purpose, qualitative research was carried out through the application of a questionnaire, with elementary school students from a public school in the city of Jundiaí in the state of São Paulo (Brazil). The research results indicate that, although elementary school students have a certain awareness of climate problems, they have generalized misconceptions about pollution and the environment. Therefore, it is increasingly necessary to invest in Environmental Education and teacher training.